DISADVANTAGES AND ADVANTAGES OF CREDIT-MODULAR TRAINING IN THE FIELD OF PHYSICAL EDUCATION (Pedagogy of Higher and Secondary Education, 2008)
The article the analysis of scientific literature dealing with the problems of the development of physical training according to the Bologna Process.